Attentional Avoidance for Guilty Knowledge Among Deceptive Individuals - Kim, Kiho; Kim, Go-eun; Lee, Jang-Han (Frontiers in Psychiatry, 2019)
The purpose of the present study is to differentiate between innocent suspects who have knowledge of crime information and guilty suspects. The study investigated eye-movement differences among three groups: a guilty group who took part in a mock crime, an innocent-aware group who did not commit a mock crime but were exposed to the crime stimuli, and an innocent-unaware group who neither committed a mock crime nor had crime-relevant information. Each group's eye movements were tracked while all participants viewed stimuli (crime-relevant, crime-irrelevant, and neutral). The results revealed that the guilty group not only viewed all stimuli later than the other groups, they also viewed crime-relevant and crime-irrelevant stimuli for a shorter time period than the innocent-aware group; the innocent-aware group focused their attention on crime-relevant and crime-irrelevant stimuli longer than neutral stimuli, and the innocent-unaware group showed no differences in their attention focus among all types of stimuli. This present study suggests that guilty individuals show attentional avoidance from all stimuli in a lie detection situation, whereas innocent-aware and innocent-unaware individuals did not show avoidance responses.